Effects of Sauropus androgynus Extract on Cognitive Function Improvement and Neuron Enhancement in Trimethyltin Chloride-Induced Rats - Kuswati, Kuswati; Ditasari, Adinda; Leony Alvionida, Rizkita; Ratu Astrid Novianti,; Nandy Muhamad Nor, Anya Roffey Vikri; Handayani, Ety Sari; Nugraha, Zainuri Sabta (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Trimethyltin chloride is a compound utilized for inducing neurotoxicity.This study is to examine effects of Sauropus androgynus (SA) on cognitive function, Bax expression, neuronal number in the hippocampus and prefrontal cortex of rats induced TMT. MATERIALS AND METHODS: This is experimental study. Its subjects were 25 males of Rattus norvegicus. The subjects were divided into five groups: group K1 (no treatment), group K2 (TMT-induced), and groups of K3, K4, and K5 (TMT-induced with ethanol extract of SA at doses of 75, 150, and 300 mg/kg body weight respectively). The TMT at a dose of 6 mg/kg body weight. Cognitive function was measured by using the Y-maze spontaneous alternation test. Brain tissue was collected for histological preparations by using toluidine blue staining and immunohistochemistry with Bax antibody. Then microscopic observations were performed to count the number of neurons and Bax expression. RESULTS: The percentage of alternation in the SA extract groups (K3, K4, K5) was higher than that in the TMT group (K2). The number of neurons in the CA1 area of the hippocampus, dentate gyrus, and prefrontal cortex in the three groups (K3, K4, and K5) was higher than that in group K2. The expression of Bax in groups of K4 and K5 was lower than that in group K2. CONCLUSION: The SA extract could improve the memory function, inhibit the Bax expression, and increase the number of neurons in the CA1 area of the hippocampus, dentate gyrus, and prefrontal cortex in the rats induced with neurotoxicity using TMT.